Analisis Biaya Operasional Dan Simpanan Dalam Memaksimalkan Sisa Hasil Usaha Pada KSP Kopdit Tuke Jung Nele - Angelica Ayu Alfreda; Emilianus Eoo Kutu Goo (AKUNTANSI 45, 2024)
The purpose of this study is to dentfy and analyze operatonal costs and savings to maximize the remaining business profits at KSP Kopdit Tuke Jung Nele for the years 2020-2022. Data collection involves nterview and documentation methods. The research employs a quantitative descriptive analysis technique. The findings indicate a decrease in operational costs, an increase n savings and improvement in business results in 2021. However, in 2022 operational costs increased, savings rose and business results declined.